2021
DOI: 10.1371/journal.pone.0254992
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotopes as a proxy for human diet and mobility from the preclassic through colonial periods in the Eastern Maya lowlands

Abstract: Maya archaeologists have long been interested in understanding ancient diets because they provide information about broad-scale economic and societal transformations. Though paleodietary studies have primarily relied on stable carbon (δ13C) and nitrogen (δ15N) isotopic analyses of human bone collagen to document the types of food people consumed, stable sulfur (δ34S) isotope analysis can potentially provide valuable data to identify terrestrial, freshwater, or marine/coastal food sources, as well as determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 142 publications
(174 reference statements)
1
9
0
Order By: Relevance
“…Sulfur isotopes in skeletal samples are used to study human diet and mobility in the Eastern Maya lowlands and Europe 265,266 using the "Longin method" of collagen extraction. 265,[267][268][269][270][271][272] Archeological bone samples are cleaned by air abrasion with Al 2 O 3 and then coarsely crushed ($1 mm) and dissolved in a 2.6 N HCl solution to eliminate mineral substances and some organic pollutants. Then the residue is heated with water (pH $ 3) at 90 C, shaken for hours, centrifuged or filtered with 5-8 μm filters, and the pure gelatine is collected.…”
Section: Skeletalmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur isotopes in skeletal samples are used to study human diet and mobility in the Eastern Maya lowlands and Europe 265,266 using the "Longin method" of collagen extraction. 265,[267][268][269][270][271][272] Archeological bone samples are cleaned by air abrasion with Al 2 O 3 and then coarsely crushed ($1 mm) and dissolved in a 2.6 N HCl solution to eliminate mineral substances and some organic pollutants. Then the residue is heated with water (pH $ 3) at 90 C, shaken for hours, centrifuged or filtered with 5-8 μm filters, and the pure gelatine is collected.…”
Section: Skeletalmentioning
confidence: 99%
“…Sulfur isotopes in skeletal samples are used to study human diet and mobility in the Eastern Maya lowlands and Europe 265,266 using the “Longin method” of collagen extraction 265,267–272 . Archeological bone samples are cleaned by air abrasion with Al 2 O 3 and then coarsely crushed (~1 mm) and dissolved in a 2.6 N HCl solution to eliminate mineral substances and some organic pollutants.…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…The main reason for this was the low S concentration in comparison to the matrix elements and an insufficient purification of S from these matrix elements. One of these matrix elements was Ti, causing potential spectral interference because of the spectral overlap of the signals of 48 Ti 16 O 2+ and 32 S + and thus, the concentration of Ti should be reduced as much as possible before MC-ICP-MS measurement. A Ti concentration decrease of approximately 57%, 91%, 49%, 41%, and 32% was observed for GBW07410, NIST 2704, BHVO-2, GBW07308, and TF sample, respectively, when using the AR leaching method compared to the AR+HF dissolution method (Table X22 in the ESI).…”
Section: Evaluation Of Digestion Proceduresmentioning
confidence: 99%
“…with the lower values typically suggesting a terrestrial and/or freshwater-based diet, while higher values indicate a marine-based diet. Similar diet and provenance studies using the δ 34 S value can be performed with humans as subjects, for which the published range is −19 to +20‰ [6], [40], [41], [42], [43], [44], [45], [46], [47], [48]. For modern humans, however, the link between sulfur isotope ratios and graphical origin of an individual may be obscured due to access to non-local food [6], [42].…”
Section: Introductionmentioning
confidence: 99%
“…Nehlich (2015) has suggested that the difference between archaeological humans and terrestrial fauna is a mere 0.8 ± 2.5‰, compared to 1-3‰ for carbon and 3-5‰ for nitrogen (DeNiro and Epstein 1978;Schoeninger and DeNiro 1984). Despite these limitations, however, sulfur isotope analyses have been used frequently -and successfully -in paleodietary studies (e.g., Ebert et al 2021;Nehlich et al 2010;Privat et al 2007;Vika 2009).…”
Section: Archaeological Applications Of δ 34 Smentioning
confidence: 99%